Satisfaction and Literacy of Telepsychiatry among Adult Patients Attending Psychiatry Outpatient Clinics in an Academic Hospital - Ahmed Albarrak; Fatima Alhaidar; Maha Alanazi; Noura Bamarei; Joud Alarifi; Nada Bin Obaid; Bayan Alhazmi (Wolters Kluwer Medknow Publications, 2024)
Introduction Telepsychiatry is an implementation of technology that delivers psychiatric care at a distance. Only a few studies have investigated the satisfaction and literacy of telepsychiatry patients in Saudi Arabia and how these factors may relate to and affect their utilization. In this study, we measured patient satisfaction across five domains: efficiency, appropriateness, effectiveness, safety, and access/timeliness. Additionally, we assessed the literacy levels of the patients. Objectives This study aimed to assess patient satisfaction with telepsychiatry among adult patients attending psychiatric clinics at an academic hospital. We would also look further into patients' literacy of telemedicine and telepsychiatry. Materials and Methods This study was conducted from June 2021 to December 2021. An electronic-based survey was used, which was carried out online by sending anonymous e-surveys to patients' phone numbers. The self-administered questionnaire was adapted from previous studies with some modifications. The survey included questions about patients' demographics, 19 questions about patients' satisfaction with telepsychiatry, and 6 questions about patients' literacy. Patients' satisfaction was measured using five domains of telehealth outcomes (access and timeliness, appropriateness, efficiency, effectiveness, and safety), in addition to assessing literacy, knowledge, and computer access. Results An electronic-based survey was sent to 300 patients who attended psychiatry clinics at an academic hospital, of these, 175 responded, resulting in a response rate of 58.3%. Among the respondents, 105 (60.0%) were female and 70 (40.0%) were male. Patients' ages ranged between 18 and 65, and 29.1% of patients were within 25-34 years. Additionally, 34.9% of patients had completed a university degree. Most of the patients also have at least one smart device. However, patients showed low levels of utilization of knowledge. Moreover, 37.1% of the patients have never used personal computers or laptops at home. In addition, two-thirds of patients have never interacted with their doctors via E-mail or social media, and half of the patients reported never using electronic services provided by the hospital. Out of 175 patients who responded and completed the patient's satisfaction survey, only 78 patients (44.6%) stated that they previously used telepsychiatry service at the hospital. Patients were generally satisfied across the five domains, 73.7% of the patients were satisfied with the appropriateness domain, followed by effectiveness (72.4%), safety (69.5%), access and timeliness (68.6%), and efficiency domain (56.4%). A significant correlation between gender and the satisfaction level was observed. No significant correlation was found between any of the other variables with literacy, knowledge, and computer access. Conclusions The study demonstrates moderate satisfaction level across the five domains, especially among males. However, for the patient's literacy and knowledge, patients have reported low levels of utilization of any form of telecommunication with their doctor or electronic services in the hospital.